Use of Emerging 3D Printing and Modeling Technologies in the Health Domain: A Systematic Literature Review - Ávila Arias, Carolina (2016)
Three-Dimensional (3D) technologies emerged from the technological advances in manufacturing required to produce physical versions of digital models. The most attractive feature of 3D technologies is that virtual models are easy to mold, and custom-made items can be physically produced. Health domains are areas in which 3D technologies have been applied, and several studies have been conducted assessing the usefulness of such technologies in those domains. In this paper we present the results of a Systematic Literature Review (SLR) on the applications of 3D technologies in the health domain. Discussion from the revision of 33 papers is presented. The main finding of this SLR is that none of the available research papers are focused on computer science related areas (i.e., all papers are published by doctors or researchers in Medicine). Moreover, all the included papers were published in journals specialized in Medicine. Therefore, they do not delve in the computational conclusions of the studies. In this article, we identified significant research gaps (from the computational perspective), as well as new ideas are being proposed on the future of 3D technologies in health.